Intensive Blood Pressure Lowering in Patients With Malignant Left Ventricular Hypertrophy - Ascher, Simon B; de Lemos, James A; Lee, MinJae; Wu, Elaine; Soliman, Elsayed Z; Neeland, Ian J; Kitzman, Dalane W; Ballantyne, Christie M; Nambi, Vijay; Killeen, Anthony A; Ix, Joachim H; Shlipak, Michael G; et al. (Journal of the American College of Cardiology, 2022)
Left ventricular hypertrophy (LVH) combined with elevations in cardiac biomarkers reflecting myocardial injury and neurohormonal stress (malignant LVH) is associated with a high risk for heart failure and death. The aim of this study was to determine the impact of intensive systolic blood pressure (SBP) control on the prevention of malignant LVH and its consequences. A total of 8,820 participants in SPRINT (Systolic Blood Pressure Intervention Trial) were classified into groups based on the presence or absence of LVH assessed by 12-lead ECG, and elevations in biomarker levels (high-sensitivity cardiac troponin T ≥14 ng/L or N-terminal pro-B-type natriuretic peptide ≥125 pg/mL) at baseline. The effects of intensive vs standard SBP lowering on rates of acute decompensated heart failure (ADHF) events and death and on the incidence and regression of malignant LVH were determined. Randomization to intensive SBP lowering led to similar relative reductions in ADHF events and death across the combined LVH/biomarker groups (P for interaction = 0.68). The absolute risk reduction over 4 years in ADHF events and death was 4.4% (95% CI: -5.2% to 13.9%) among participants with baseline malignant LVH (n = 449) and 1.2% (95% CI: 0.0%-2.5%) for those without LVH and nonelevated biomarkers (n = 4,361). Intensive SBP lowering also reduced the incidence of malignant LVH over 2 years (2.5% vs 1.1%; OR: 0.44; 95% CI: 0.30-0.63). Intensive SBP lowering prevented malignant LVH and may provide substantial absolute risk reduction in the composite of ADHF events and death among SPRINT participants with baseline malignant LVH.